Intellectus possibilis y multitudo: las fuentes filosóficas del averroísmo político en Monarchia de Dante Alighieri - Nuria Sánchez Madrid (Medievalista)
The paper suggests a reading about Dante’s acceptance of the Averroist thesis about the unity of intellect in his political work Monarchia. I consider the philosophical sources of discussion of this thesis in the second half of the thirteenth century, among which I specially focus on its refutation by Thomas Aquinas and on its nuanced admission by Siger of Brabant. I argue that the distinction between the universality and unity of the possible intellect and the plurality of received forms by the imagination of each individual, a position suggested by Siger of Brabant, is the clue of the use that Dante makes of monopsychism in Monarchia, an appraisal that gives birth to a new model of human community signally immanent and secular.